The Health-Promoting Potential of Salix spp. Bark Polar Extracts: Key Insights on Phenolic Composition and In Vitro Bioactivity and Biocompatibility - Ramos, Patrícia A. B.; Moreirinha, Catarina; Silva, Sara; Costa, Eduardo M.; Veiga, Mariana; Coscueta, Ezequiel; Santos, Sónia A. O.; Almeida, Adelaide; Pintado, M. Manuela; Freire, Carmen S. R.; Silva, Artur M. S.; Silvestre, Armando J. D. (Antioxidants, 2019)
Salix spp. have been exploited for energy generation, along with folk medicine use of bark extracts for antipyretic and analgesic benefits. Bark phenolic components, rather than salicin, have demonstrated interesting bioactivities, which may ensure the sustainable bioprospection of Salix bark. Therefore, this study highlights the detailed phenolic characterization, as well as the in vitro antioxidant, anti-hypertensive, Staphylococcus aureus growth inhibitory effects, and biocompatibility of Salix atrocinerea Brot., Salix fragilis L., and Salix viminalis L. bark polar extracts. Fifteen phenolic compounds were characterized by ultra-high-performance liquid chromatography-ultraviolet detection-mass spectrometry analysis, from which two flavan-3-ols, an acetophenone, five flavanones, and a flavonol were detected, for the first time, as their bark components. Salix bark extracts demonstrated strong free radical scavenging activity (5.58–23.62 µg mL−1 IC50 range), effective inhibition on angiotensin-I converting enzyme (58–84%), and S. aureus bactericidal action at 1250–2500 µg mL−1 (6–8 log CFU mL−1 reduction range). All tested Salix bark extracts did not show cytotoxic potential against Caco-2 cells, as well as S. atrocinerea Brot. and S. fragilis L. extracts at 625 and 1250 µg mL−1 against HaCaT and L929 cells. These valuable findings can pave innovative and safer food, nutraceutical, and/or cosmetic applications of Salix bark phenolic-containing fractions.